Virtual and Mixed Reality - New Trends International Conference, Virtual and Mixed Reality 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011, Proceedings, Part I - Shumaker, Randall; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNCS 6773-6774 constitutes the refereed proceedings of the International Conference on Virtual and Mixed Reality 2011, held as Part of HCI International 2011, in Orlando, FL, USA, in July 2011, jointly with 10 other conferences addressing the latest research and development efforts and highlighting the human aspects of design and use of computing systems. The 43 revised papers included in the first volume were carefully reviewed and selected from numerous submissions. The papers are organized in the following topical sections: augmented reality applications; virtual and immersive environments; novel interaction devices and techniques in VR; human physiology and behavior in VR environments.
Keywords: Computer science; Software engineering; Information systems; Multimedia systems; Artificial intelligence; Computer graphics; Computer Science; User Interfaces and Human Computer Interaction; Computer Graphics; Artificial Intelligence (incl. Robotics).; Special Purpose and Application-Based Systems; Information Systems Applications (incl.Internet).; Multimedia Information Systems